The NIH genetic testing registry: a new, centralized database of genetic tests to enable access to comprehensive information and improve transparency - Rubinstein, Wendy S.; Maglott, Donna R.; Lee, Jennifer M.; Kattman, Brandi L.; Malheiro, Adriana J.; Ovetsky, Michael; Hem, Vichet; Gorelenkov, Viatcheslav; Song, Guangfeng; Wallin, Craig; Husain, Nora; Chitipiralla, Shanmuga; et al. (Nucleic acids research, 2013)
The National Institutes of Health Genetic Testing Registry (GTR; available online at http://www.ncbi.nlm.nih.gov/gtr/) maintains comprehensive information about testing offered worldwide for disorders with a genetic basis. Information is voluntarily submitted by test providers. The database provides details of each test (e.g. its purpose, target populations, methods, what it measures, analytical validity, clinical validity, clinical utility, ordering information) and laboratory (e.g. location, contact information, certifications and licenses). Each test is assigned a stable identifier of the format GTR000000000, which is versioned when the submitter updates information. Data submitted by test providers are integrated with basic information maintained in National Center for Biotechnology Information's databases and presented on the web and through FTP (ftp.ncbi.nih.gov/pub/GTR/_README.html).